2006
DOI: 10.1677/joe.1.06195
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide W is present in antral G cells of rat, mouse, and human stomach

Abstract: Neuropeptide W (NPW) is a 30-amino-acid peptide initially isolated from the porcine hypothalamus as an endogenous ligand for the G protein-coupled receptors GPR7 and GPR8. An intracerebroventricular administration of NPW increased serum prolactin and corticosterone concentrations, decreased dark-phase feeding, raised energy expenditure, and lowered body weight. Peripherally, GPR7 receptors are abundantly expressed throughout the gastrointestinal tract; the presence of NPW in the gastrointestinal endocrine syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…The presence of NPW protein in the stomach is consistent with the results of Mondal et al (2006Mondal et al ( , 2008, who identified NPW in the antral gastrin (G) cells of rat, mouse, and human stomachs and suggested that NPW has a physiological role in the development of the rat stomach. They also reported a decrease in NPW levels in the stomachs of fasting animals and a subsequent increase upon refeeding (Mondal et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…The presence of NPW protein in the stomach is consistent with the results of Mondal et al (2006Mondal et al ( , 2008, who identified NPW in the antral gastrin (G) cells of rat, mouse, and human stomachs and suggested that NPW has a physiological role in the development of the rat stomach. They also reported a decrease in NPW levels in the stomachs of fasting animals and a subsequent increase upon refeeding (Mondal et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, ghrelin and obestatin are produced in the gastric endocrine cells of the P/D 1 type in humans, A-like type in rats and X type in dogs [1][2][3][4]. Gastrin-producing antral G cells were recently found to also produce neuropeptide W [5], and enterochromaffin-like cells in the oxyntic mucosa produce pancreastatin (chromogranin A fragment) and histamine [6][7][8]9 ]. Gastric D cells in the antrum (open type) and in the oxyntic mucosa (close type) produce somatostatin, and the enterochromaffin cells produce serotonin.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of its components was observed by others in the brain and alimentary tract (2,(7)(8)(9)(10)(11)(12)(13)(14). Both NPB and NPW affect food intake and energy expenditure (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 77%